New approaching application of deschooling education - Gündüz, Mustafa (My University, 2007)
This study is an evaluation of the tutoring that new and different method in deschooling education. The main concern of the study was what tutoring is, which methods should be used in tutoring, its advantage and disadvantages and what tutoring brings into the field of educational sciences. Additionally study investigates the fundamental claims of tutoring and its validity. Importance of tutoring in the world and Turkey was also mentioned. in the study. As a new teaching and leaming methods of post-modern society tutoring, compared with historical background and deschooling in the article. Tutoring has been taken into consideration as a different version of deschooling society and home schooling.
Okulsuz e?itim uygulamasina ilişkin yeni yaklaşimlar
Keywords: Deschooling education; Deschooling society; Home schooling